1976
DOI: 10.2337/diab.25.10.975
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing Release Hormone Tests in Impotent Diabetic Males

Abstract: Assessment of pituitary-gonadal function was made in impotent diabetic males using luteinizing hormone-release hormone tests. Serum testosterone, sex-hormone-binding globulin capacity, and basal and incremental gonadotrophin concentrations in the impotent diabetics were similar to those in control diabetics, suggesting a primary neurologic rather than an endocrine defect as the cause of the impotence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Some patients do in fact later develop other features of autonomic neuropathy and abnormal tests [105,172]. Despite earlier reports [167,168] there is no evidence that endocrine dysfunction contributes and recent studies showed normal plasma gonadotrophins [173,174] and testosterone [175] in diabetics with impotence.…”
Section: Urogenital Systemmentioning
confidence: 99%
“…Some patients do in fact later develop other features of autonomic neuropathy and abnormal tests [105,172]. Despite earlier reports [167,168] there is no evidence that endocrine dysfunction contributes and recent studies showed normal plasma gonadotrophins [173,174] and testosterone [175] in diabetics with impotence.…”
Section: Urogenital Systemmentioning
confidence: 99%
“…In experimental, streptazotocin induced, diabetes in rats, plasma T levels were decreased, but it is difficult to exclude a direct effect of streptazotocin. Charrau et al (1978) reported a decreased LH binding capacity of Leydig cells, whereas several groups (Kent 1966;Wright et al 1976) reported normal testosterone levels in male diabeucs; others (Gattucio et al 1978) reported low plasma T and reduced response to hCG whereas Ando et al (1978) reported sex hormone levels in diabetics to be similar to those found in elderly men.…”
Section: E Catecholamines and Neurotransmittersmentioning
confidence: 98%
“…However, there are few and conflicting data assessing pituitary gonadal function in diabetic patients with and without impotence. Rastogi et al (1974) demonstrated normal gonadotropin response to GnRH in diabetic men with and without impotence, while Wright et al (1976) and Shahwan et al (1978) have shown reduced LH response to GnRH in impotent diabetic male patients. Distiller et al (1975), studying male and female diabetic patients, demonstrated reduced LH response to GnRH at 30 minutes in the females and at 30 and 120 minutes in the males.…”
Section: Introductionmentioning
confidence: 99%